SAT0216 Sensitivity and Specificity of Optical Spectral Transmission Imaging in Detecting Joint Inflammation in Rheumatoid Arthritis. (10th June 2014) - Krabbe, S.; Danielsen, M.A.; Østergaard, M.; Giard, M.-C.; Terslev, L.
Abstract : Background: A fast, physician-independent, sensitive, reproducible tool for assessment of disease activity would be useful in rheumatoid arthritis (RA) clinical practice. Objectives: This study aimed to compare a new technique, optical spectral transmission imaging (OST), and clinical examination with colour Doppler (CD) ultrasound as gold standard reference. Primary outcomes were sensitivity and specificity of OST for joint inflammation at joint level, and correlations of the summation of joint scores at patient level. Methods: This cross-sectional study included 62 RA patients, 50 with ≥1 clinically swollen joint in the hands or wrists and 12 patients without tender or swollen joints. Joint examination, patient global VAS, HAQ and CRP were registered. OST was obtained by Hemics Full Hand Proto at two wavelengths (660nm and 810nm) before, during and after the inflation of a pressure cuff to 50 mm Hg for 60 seconds (total duration of examination 1.5 minutes). OST scores for each joint were based on a previously developed algorithm aimed to mimic a combination of Doppler and grey-scale synovitis, using a predefined cutoff of 0.521 for inflammatory activity. A GE Logiq® E9 US machine with a 5-16ML linear array transducer and Doppler setting optimized for slow flow was used for grading CD activity (0-3) in wrist joints, metacarpophalangeal joints (MCPs) and proximal interphalangeal joints (PIPs). CD activity ≥1 was used as gold standard for inflammation. CD, OST and clinical data were obtained separately and blinded to other data. Results: CD activity ≥1 was observed in 167 (12%) of 1364 joints. An OST score larger than the predefined cut-off of 0.521 was found in 343 (25%) joints. AUC of the ROC curve of OST score vs. the gold standard reference was 0.690, p<0.001. For all joints, using cut-offs of 0.145 (wrists)/0.103 (MCPs)/0.697 (PIPs) as optimized for a sensitivity of 75% for the individual joint areas, specificity was 42%. Using cut-offs of 0.525/0.951/1.293 as optimized for a specificity of 90% for the individual joint areas, sensitivity was 23%. At the patient level, the OST score correlated with CD (rho=0.28, p=0.03), patient global VAS (rho=0.31, p=0.02), DAS28 (rho=0.29, p=0.02) and HAQ (rho=0.26, p=0.04). Using new cutoffs as described above, we found even tighter correlations at the patient level with CD (rho=0.31, p=0.01), SJC (rho=0.28, p=0.03), patient global VAS (rho=0.41, p=0.001), CRP (rho=0.29, p=0.03), DAS28 (rho=0.40, p=0.001) and HAQ (rho=0.48, p<0.001). Conclusions: Significant correlations with clinical and CD measures of joint inflammation documented the construct validity of OST assessment of joint inflammation. However, with CD as gold standard reference, OST did not demonstrate improved sensitivity and specificity compared to clinical joint examination. Further analyses of the data, including ultrasound grey-scale synovitis, are pending. After further development, OST may be a feasible technique for quick, physician-independent, non-invasive assessment of joint inflammation in RA. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4364